Sosialisasi Penggunaan Aplikasi GeoGebra dalam Meningkatkan Minat BelajarSiswa Kelas VI pada Pelajaran Bangun Ruang di SDIT Buah Hati Padang - Mishbah Ulhusna; Lili Rismaini; Syelfia Dewimarni (Jurnal Pengabdian Masyarakat Indonesia Sejahtera, 2023)
Community Service (PKM) is one of the forms of Higher Education's Tri Dharma. PKM is proposed to carry out activities that focus on socialization and education. Learning mathematics is about understanding abstract ideas or concepts, structures, and their logically and systematically organized relationships. Media is a communication component that serves as a carrier of messages from the communicator to the communicant. One of the learning media used to facilitate students is the Geogebra application. Geogebra is a computer application created to facilitate mathematics learning, especially in geometry, algebra, and calculus subjects. By using the Geogebra application, it can improve students' mathematics learning outcomes. The method used in this PKM is education and direct practice of the "jarimatika" method in multiplication problems. As a result, participants become more understanding of the Geogebra application.